Limited-Dissection Ligament-Preserving Facelift for Early Facial Aging: Surgical Technique and Clinical Experience - Albert Bosch; Nabil Fakih-Gomez (Aesthetic Surgery Journal Open Forum, 2026)
Abstract Background Early facial aging is characterized by midfacial descent, loss of mandibular definition, and attenuation of retaining ligaments. Although SMAS-based and deep-plane facelifts remain the gold standard, many patients seek less invasive procedures with shorter recovery. Objectives To describe a limited-dissection ligament-preserving facelift technique and evaluate its safety and clinical outcomes in patients with early facial aging. Methods A retrospective case series of 100 patients treated between June 2021 and January 2025 was performed. All procedures were carried out under local anesthesia using limited dissection and superoposterior suspension of the SMAS-ligament complex and platysma. Outcomes included complications, revision rates, recovery time, and patient satisfaction at one year. Results Mean patient age was 43.4 years (range, 34–52 years). All procedures were performed under local anesthesia without sedation. Recovery was rapid, with 96% of patients resuming normal activities within 7 days. Transient hypoesthesia occurred in 22% of patients and resolved within 8 weeks. No hematoma, infection, permanent nerve injury, or wound dehiscence was observed. Temporal alopecia occurred in 14% of patients and resolved spontaneously in most cases. Minor under-correction was observed in 6%, with an overall revision rate of 9%. At one year, 82% of patients reported being satisfied or very satisfied. Conclusions Limited-dissection ligament-preserving facelift appears to be a safe and effective minimally invasive option for selected patients with early facial aging. It provides natural results, rapid recovery, and may represent an intermediate approach between non-surgical treatments and traditional facelift procedures.